Negative electrorheological fluids - Ko, Young Gun; Choi, Ung Su (JOURNAL RHEOLOGY AMER INST PHYSICS, 2013)
Electrorheological (ER) fluids are electroresponsive materials that have been extensively investigated for several decades. Despite negative ER fluids being one of the most promising new class of candidate materials for various potential applications, only positive ER fluids have been widely used thus far. Herein, we briefly review the negative ER fluids to encourage their application in commercial device manufacture. This short review discusses an overview of mechanisms, materials, and applications of negative ER fluids. (C) 2013 The Society of Rheology.